Advanced introduction to pricing strategy and analytics - Rao, Vithala R. (Cheltenham : Edward Elgar Publishing, 2023)
This Advanced Introduction explores strategies of pricing products (goods and services) that can be employed by a firm. The analytical techniques and data necessary for implementing the pricing strategies are described in an easy-to-understand manner, along with examples. Pricing strategies covered include cost-plus, reference value pricing, product line pricing, pricing product bundles, pricing over time, pricing under competition, and subscription pricing.
Keywords: Business & Economics / Marketing / General; Business & Economics / Sales & Selling / General; Business statistics